2022
DOI: 10.2147/jir.s377499
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ Promotes LPS-Induced IL-1β Transcription and Secretion in Alveolar Macrophages via NOD2 Signaling

Abstract: Objective C/EBPβ, a crucial transcription factor, regulates innate immunity and inflammatory responses. However, the role played by C/EBPβ in alveolar macrophage (AM) inflammatory responses remains unknown. This study aimed to investigate the role and mechanism of C/EBPβ in alveolar macrophages (AMs) from the transcriptional level and to search for natural compounds targeting C/EBPβ. Methods Rat AMs were infected with Lv-sh-C/EBPβ and treated with LPS, and the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In line with our study, another study has also observed HFD-induced neuroinflammation occurred via the C/EBPβ/AEP pathway ( Liu et al, 2022 ). Meanwhile, C/EBPβ also promoted lipopolysaccharide-induced IL-1β transcription and secretion in alveolar macrophages ( Luo et al, 2022 ), indicating a bidirectional relationship between inflammatory cytokines and C/EBPβ. Furthermore, clinical research showed that patients with depression had elevated IL-1β, IL-6, and TNF-α levels ( Connor and Leonard, 1998 ; Maes et al, 1999 ; Mikova et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our study, another study has also observed HFD-induced neuroinflammation occurred via the C/EBPβ/AEP pathway ( Liu et al, 2022 ). Meanwhile, C/EBPβ also promoted lipopolysaccharide-induced IL-1β transcription and secretion in alveolar macrophages ( Luo et al, 2022 ), indicating a bidirectional relationship between inflammatory cytokines and C/EBPβ. Furthermore, clinical research showed that patients with depression had elevated IL-1β, IL-6, and TNF-α levels ( Connor and Leonard, 1998 ; Maes et al, 1999 ; Mikova et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%